“ALPAMÍS” DÁSTANÍNDA QAHARMAN HÁM ANTI - QAHARMAN OBRAZLAR ANALIZI (Barshınay ham Surxayl-mástan obrazları mısalında) - Allambergenova, Nodira Gulmurzaevna (SCIENCE and SOCIETY, 2026)
The heroes of the Alpamysh epic, especially the main characters, are thoroughly developed in every respect, thoroughly and fully complying with the laws of art. The fact that characters such as Alpamysh, Barchinoy, Boybori, Boysari, Karajon, Kaldirgoch Kultoy, Surkhayl, Kayqubad, Tovka, and Yodgor are endowed with their own unique traits and characteristics, and the consistency of their thoughts and actions with the logic of life brings them closer to realistic images. These same qualities in folk heroes require a detailed, scientific, and theoretical approach. This article analyzes the images of one of the main characters of the Alpamysh epic – Barchinoy, the archetype of the Alpine woman, and Surkhayl, the antihero, the embodiment of cunning.